Direct democracy and institutional trust: relationships and differences across personality traits - Freitag, Markus; Ackermann, Kathrin (Political psychology, 2016)
Direct democracy plays a prominent role in the explanation of institutional trust. To date, however, empirical findings on the effects of direct democracy remain inconclusive. In this article, we argue that this inconclusiveness can be partly ascribed to the diverse effects direct democracy has on individuals. In other words, direct democracy influences institutional trust, but how and to what degree depends on individuals’ personality traits. Running hierarchical analyses of unique survey data from a random sample of eligible Swiss voters, we document three findings: First, we show that the number of ballot measures is not directly associated with institutional trust. Second, we demonstrate that the Big Five personality traits affect the propensity to trust. Third, some of these traits also alter the relationship between direct democracy and institutional trust, suggesting that certain personality types are more likely to be sensitive to popular votes than others and that not everyone is equally likely to respond to political stimuli, even in highly democratic environments.
First published: 01 September 2015
Gesehen am 14.04.2021